PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING PADA MENULIS PUISI DI SMA PASUNDAN 7 BANDUNG BERBANTUAN MEDIA CANVA - Kamilia Mutiara Amir; Eggie Nugraha; Meity Suratiningsih (STKIP Subang, 2023)
This research was conducted due to the low ability of students when writing poetry texts, which was caused by a lack of self-confidence, difficulties when choosing words, and the use of less creative learning methods by educators. One of the learning methods that can increase students' creativity is the contextual teaching and learning (CTL) method. The purpose of this study was carried out to evaluate the ability of researchers when conducting research and applying the CTL method when learning to write poetry texts, students' abilities when writing poetry, students' abilities when writing poetry using the CTL method, as well as comparisons of students' abilities before and after being given contextual method treatment teaching and learning. The research method used was an experiment with a true experimental pretest-posttest control group design. The results of this study indicate that; 1) the researcher succeeded in carrying out learning to write poetry texts using the CTL method with a value of 37.2. 2) the condition of the students before being given the CTL method treatment. 3) the condition of the students after being given the CTL method. 4) differences in students' abilities before and after being given the CTL method treatment.